Determination of model parameters of PV modules using a low cost I-V tracer - Leite, Vicente (2012)
Tracing current-voltage characteristics of photovoltaic modules in open field conditions is a very important task in degradation and fault diagnosis. Usually this is done by using expensive DC electronic loads, many times not suitable for outdoor tests. The health state of photovoltaic modules can be evaluated by monitoring the parameters of its exponential model, mainly the series resistance. This can be done by tracing the current-voltage characteristics in field conditions from which those model parameters can be extracted. This paper presents the determination of the parameters of the exponential model of photovoltaic modules from experimental current-voltage curves using a low cost I-V tracer developed in previous works.